2004
DOI: 10.1099/jmm.0.05326-0
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility testing of sequential isolates of Aspergillus fumigatus recovered from treated patients

Abstract: Two-hundred sequential Aspergillus fumigatus isolates recovered from 26 immunocompromised patients with invasive aspergillosis or bronchial colonization were tested for their in vitro susceptibility to posaconazole, itraconazole, voriconazole, terbinafine and amphotericin B. Twentyone patients were treated with amphotericin B and/or itraconazole. Antifungal susceptibilities of the isolates recovered before treatment were not significantly different from those of isolates recovered after the onset of antifungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…These data indicate that the emergence of resistance to amphotericin B is uncommon during therapy for invasive aspergillosis (137). These findings were confirmed in a larger study analyzing 200 sequential A. fumigatus isolates from 26 patients which determined that the MICs to amphotericin B (n ϭ 100) or itraconazole (n ϭ 91) were similar both pre-and postexposure, leading to the conclusion that the emergence of resistance while on therapy was infrequent (45).…”
Section: Resistance To Drugs Exerting Cell Membrane Stress: the Polyenessupporting
confidence: 68%
“…These data indicate that the emergence of resistance to amphotericin B is uncommon during therapy for invasive aspergillosis (137). These findings were confirmed in a larger study analyzing 200 sequential A. fumigatus isolates from 26 patients which determined that the MICs to amphotericin B (n ϭ 100) or itraconazole (n ϭ 91) were similar both pre-and postexposure, leading to the conclusion that the emergence of resistance while on therapy was infrequent (45).…”
Section: Resistance To Drugs Exerting Cell Membrane Stress: the Polyenessupporting
confidence: 68%
“…Itraconazole resistance in A. fumigatus has been correlated with clinical failure in both humans and experimental animal models of infection (71). However, clinical failure in invasive aspergillosis may have many causes other than drug resistance; furthermore, in patients who have died from inva-sive aspergillosis despite amphotericin treatment, emergence of resistance to amphotericin or itraconazole during treatment has not been detected (65,207). In a review of 11 patients with hematologic malignancies in whom A. fumigatus or A. flavus was isolated, while on amphotericin, resistance to amphotericin was not detected, but it was thought that poor drug penetration to the site of infection may have been a contributor to failure (238).…”
Section: Management In Vitro Susceptibility To Antifungal Agentsmentioning
confidence: 99%
“…Nonmyeloablative transplants in which engraftment is achieved with reduced-intensity conditioning regimens have now emerged as an important therapeutic modality in HSCT recipients (87,135,197,208,329). Between 1998 and 2000, there has been an approximately fivefold [63][64][65][66][67] increase in the number of nonmyeloablative transplants; these less intensive conditioning regimens are now used in about 25% of the allogeneic transplants in some institutions (132). Nonmyeloablative conditioning comprises a wide spectrum of reduced-intensity regimens.…”
Section: Epidemiology Hematopoietic Stem Cell Transplant Recipientsmentioning
confidence: 99%
“…The role of the azoles in the development of resistance has not yet been clarified. Although some authors have reported a role of azoles in the development of resistance in Aspergillus (3,5,11,15), other authors found itraconazole-resistant strains before exposure to the drug (7) or did not find resistant strains even in patients receiving azoles (6).…”
mentioning
confidence: 99%